1996
DOI: 10.1038/384474a0
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor GATA-3 is required for development of the T-cell lineage

Abstract: THE zinc-finger transcription factor GATA-3 is expressed in haematopoietic cells and in the developing kidney and nervous system. Within the haematopoietic lineages, expression of GATA-3 is restricted to thymocytes and T cells. Functionally important GATA-3 binding sites have been identified in multiple T-cell-specific genes. Mice containing homozygous null mutations of the GATA-3 gene die on embryonic day 12, precluding a detailed assessment of the role of GATA-3 in haematopoietic development. Here we have us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
349
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(359 citation statements)
references
References 30 publications
6
349
0
4
Order By: Relevance
“…Furthermore, GATA-3 is involved in multiple stages of CD4 T cell development. First, GATA-3-deficient hematopoietic stem cells fail to generate T cells in transfer experiments [41]. Second, using conditional Gata3 knockout mice, it was observed that deletion in CD4/CD8 double-negative thymocytes blocked T cell development at the DN3 stage [42].…”
Section: The Central Role Of Gata-3 In Reinforcing Th2 Responsesmentioning
confidence: 99%
“…Furthermore, GATA-3 is involved in multiple stages of CD4 T cell development. First, GATA-3-deficient hematopoietic stem cells fail to generate T cells in transfer experiments [41]. Second, using conditional Gata3 knockout mice, it was observed that deletion in CD4/CD8 double-negative thymocytes blocked T cell development at the DN3 stage [42].…”
Section: The Central Role Of Gata-3 In Reinforcing Th2 Responsesmentioning
confidence: 99%
“…The embryonic lethality of Gata3 -/-mutant mice at day 11 of gestation [8] and the failure of Gata3 -/-ES cells to contribute to the T cell compartment in Rag2 -/-or WT chimeric mice [5,9] precluded the analysis of GATA3 function in murine T cell development in vivo. Conditional deletion of the Gata3 gene at the DN stage using the Cre-loxP system, whereby the Cre transgene was driven by the proximal Lck promoter, resulted in a developmental arrest at the CD25 + CD44 -DN3 stage, implicating GATA3 in b-selection [10].…”
Section: Introductionmentioning
confidence: 99%
“…GATA1, for example, was originally identified as an activator of globin gene expression and was subsequently shown to be involved in the regulation of virtually every erythroid-specific gene examined to date (for review, see Orkin 1992). Targeted disruption of the GATA1, GATA2, and GATA3 genes in the mouse has demonstrated that each is an important regulator that establishes the identity of the hematopoietic lineage in which it is expressed (Penvy et al 1991;Tsai et al 1994;Pandolfi et al 1995;Ting et al 1996). Loss of GATA1 results in the absence of mature erythroid cells but not megakaryocytes or mast cells (Pevny et al 1991;Blobel et al 1995), whereas the loss of GATA2 results in a deficit in hematopoietic progenitor cells (Tsai et al 1994).…”
mentioning
confidence: 99%